Oxytocin induces differentiation of P19 embryonic stem cells to cardiomyocytes - Paquin, Joanne (National Academy of Sciences, 2002)
We recently discovered the existence of the oxytocin/oxytocin receptor (OT/OTR) system in the heart. Activation of cardiac OTR stimulates the release of atrial natriuretic peptide (ANP), which is involved in regulation of blood pressure and cell growth. Having observed elevated OT levels in the fetal and newborn heart at a stage of intense cardiomyocyte hyperplasia, we hypothesized a role for OT in cardiomyocyte differentiation. We used mouse P19 embryonic stem cells to substantiate this potential role. P19 cells give rise to the formation of cell derivatives of all germ layers. Treatment of P19 cell aggregates with dimethyl sulfoxide (DMSO) induces differentiation to cardiomyocytes. In this work, P19 cells were allowed to aggregate from day 0 to day 4 in the presence of 0.5% DMSO, 10(−7) M OT and/or 10(−7) M OT antagonist (OTA), and then cultured in the absence of these factors until day 14. OT alone stimulated the production of beating cell colonies in all 24 independently growing cultures by day 8 of the differentiation protocol, whereas the same result was obtained in cells induced by DMSO only after 12 days. Cells induced with OT exhibited increased ANP mRNA, had abundant mitochondria (i.e., they strongly absorbed rhodamine 123), and expressed sarcomeric myosin heavy chain and dihydropyridine receptor-α1, confirming a cardiomyocyte phenotype. In addition, OT as well as DMSO increased OTR protein and OTR mRNA, and OTA completely inhibited the formation of cardiomyocytes in OT- and DMSO-supplemented cultures. These results suggest that the OT/OTR system plays an important role in cardiogenesis by promoting cardiomyocyte differentiation.